1993
DOI: 10.1177/154079699301800103
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Integrated Educational Placement of Students with Severe Disabilities

Abstract: A study, usingsurvey methodology, wasconducted to identify factors associated with the integrated educational placement of students with severe disabilities. Questionnaires were completed by the families and teachers of1,009 students from five participating states. The questionnaires were designed to measure 19 variables that integration literature suggests are predictive of integrated placement. Logistical regression procedures were utilizedto determine the probability ofintegrated placement as a function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Thousand and Villa (1995), for example, suggest that vision is one of the five variables essential to successful inclusion (although they give conflicting messages about who can provide it). Similarly, others have found that teacher and administrator advocacy for inclusion is significantly associated with integrated placements for students with severe disabilities (Hunt et al, 1993).…”
Section: Theoretical Frameworkmentioning
confidence: 91%
“…Thousand and Villa (1995), for example, suggest that vision is one of the five variables essential to successful inclusion (although they give conflicting messages about who can provide it). Similarly, others have found that teacher and administrator advocacy for inclusion is significantly associated with integrated placements for students with severe disabilities (Hunt et al, 1993).…”
Section: Theoretical Frameworkmentioning
confidence: 91%
“…According to teacher and family ratings, teacher advocacy for integration is the variable most strongly related to integrated placement (Hunt et al, 1993). However, research has shown that although many novice teachers do express beliefs favoring the inclusion of children of diverse educational needs in their classrooms, two impediments to this goal have been documented: (a) lack of training, and (b) lack of models of successful inclusive education (Tomlinson et al, 1997).…”
Section: Effects Of Experience On Teachermentioning
confidence: 99%
“…While studies have emerged that consider parent views of general class placements for their children with sensory impairments (Giangreco et al, 1991), as well as parent perceptions regarding such practices as the placement of students with severe disabilities into programs on general education campuses (Guralnick, Conner, & Hammond, 1995;Hunt et al, 1993;McDonnell, 1987;Miller et aI., 1992), to date there are no published empirical studies specifically addressing parent perceptions of the efficacy of including their own children with significant cognitive disabilities into general education classrooms. The unavailability of such research may be in part due to the lack of a formal attitudinal scale designed Exceptional Children to measure such perceptions.…”
mentioning
confidence: 98%